INFLUENCE OF SOME SULPHATED POLYSACCHARIDES ON THE PLATELET AGGREGATION IN NORMAL AND IN PATIENTS WITH ISCHEMIC HEART DISEASE - K.E., Nasirov; M.K, Musaeva; N.N, Khoshimov; G.M, Raimova; S, Turaev A.; B.I., Muhitdinov (International Journal of Psychosocial Rehabilitation, 2020)
Purpose of the research: To study the effect of various modified sulfated polysaccharides on platelet aggregation activity in normal and in patients with coronary heart disease (CHD). Materials and methods: Platelet aggregation was recorded on a Biol ALAT-2 220LA aggregometer (Russia) on rich plasma of a healthy person and coronary heart disease. Platelet aggregation inducers used were ADP (2 μM), adrenaline (5 μM), and collagen and ristomycin (0.5 u / ml) (Sigma). Results: The degree of aggregation with the addition of ADP or adrenaline inducers in the blood plasma of a healthy person and coronary heart disease is shown, depending on. In contrast to ADP and adrenaline-induced aggregation, in collagen or ristomycin-induced aggregation, in the blood plasma of a healthy person and CHD, an almost identical single-phase, irreversible curve was observed, which shows that collagen and ristomycin-induced platelet aggregation do not change significantly. When studying the effect of compounds CC-BOS-122, CC-GSC-63, CC-GSC-14 on platelet aggregation in healthy human plasma and coronary heart disease, it was shown that the compound CC-BOS-122 has the most pronounced activity. Conclusions: The studied compounds CC-BOS-122, CC-GSC-63, and CC-GSC-14 have the greatest effect on the activity of glycoprotein receptors on the platelet membrane due to the mobilization of calcium ions from intracellular depots.